A socially responsible decision‐making model for firms contracting with constrained farmers. (7th February 2022) - Dutta, Nilanjan; Kaur, Arshinder
Abstract: In emerging economies, farming contracts with collateral‐free credits are essential in linking the poor producers to the mainstream agri‐supply chains (SCs). Thus, we frame a decision‐making model for a firm procuring through advance‐payment contracts (APCs) from numerous small farmers. These farmers are decision‐biased and have varying needs for credit. Hence, composed of a fraction of the per unit guaranteed price, the advance payment uniquely affects the farmers' realized yields. We model the contracting scenario assuming the farmers as reference‐dependent loss‐averse newsvendors facing random yields who are allowed to commit their supply quantities; and the firm as a risk‐neutral profit‐maximizer, encountering demand stochasticity. We then analyze the association of the farmer's optimal commitment and the firm's optimal number of contracted farmers with the contract's parameters. Subsequently, given the information asymmetry on farmers' cost and behavioral attributes, we design a menu of contracts based on the contract theory. The menu simultaneously aims to maximize the firm's expected profit while meeting the welfare needs of the smallholders having the highest requirement for an advance. Finally, we use existing data on the model's parameters value to numerically illustrate its applicability. The illustration could demonstrate the customarily observed practice of excluding smallholders from contractual arrangements featuring no‐APCs. It also exhibited a menu's dominance over a single contract in meeting the SC entities' mutual needs and its usability in promoting socially responsible operations. We believe that firms and policy makers would find these analyses helpful in designing socioeconomically viable agri‐SCs contracts.